Onshore tsunami sediment transport mechanisms inferred from heavy mineral assemblages. (May 2015) - Costa, Pedro JM; Andrade, Cesar; Cascalho, João; Dawson, Alastair G; Freitas, Maria C; Paris, Raphael; Dawson, Sue
The aim of this study is to discuss and to extend the characterization of (palaeo)tsunami deposits, and their source materials, based upon the detailed study of their heavy mineral assemblages. Results obtained from three distinct locations (Portugal, Scotland and Indonesia), different coastal contexts and chronologies (the tsunami events studied took place at 1500 cal. yr BP, AD 1755 and 2004) are summarized and discussed in order to contribute to the sedimentological study of onshore (palaeo)tsunami deposits. Results indicate that heavy mineral assemblages primarily reflect local specific conditions. For example, in the Portuguese sites, ca. 90% of the heavy mineral population consists of tourmaline+andalusite+staurolite, whereas in the Scottish samples garnet+amphiboles can be dominant in 90% of the assemblage, where at the Indonesian study site amphiboles+andalusite were the most frequent minerals. The application of Principal Component Analysis for each site reveals that the first two components explain at least 55% of the total variance. In the three studied areas, hydraulic sorting by density was observed and a higher presence of the denser heavy minerals of the assemblages was detected. However, it is important to stress that the sediment source plays a key role in the establishment of the heavy mineral assemblages of the (palaeo)tsunami deposits. In this study, relationships between the likely source sediments and the (palaeo)tsunami deposits were described and whenever possible sediment sources were clearly identified. Furthermore, it was also possible to detect the backwash signal using the analysis of the heavy minerals (e.g. higher frequency of denser minerals or variation in the presence of rounded or euhedral zircon). The work presented here, in contributing to the enhancement of sedimentological criteria presently available to recognize and differentiate extreme marine inundation deposits, also highlights new areas for future research.